Senescence in strains of Neurospora from southern India - Ramesh Maheshwari; Bhuvana Kannan; Alka Pandit (Fungal Genetics Reports, 1994)
Natural isolates of Neurospora which cannot be vegetatively propagated continuously have been identified among collections from distant geographical locations (X. Yang and A.J.F. Griffiths 1993 Mol. Gen. Genet. 237:177-186). We have found that senescence is common in strains of N. intermedia growing on burned sugar cane in fields in Maddur, approximately 80 km southwest of Bangalore. In a survey of 150 strains, 29 strains have died to date in 57 serial subcultures made at intervals of 5-10 days on slants of Vogel's N medium + 1.5% sucrose. Senescence was first observed after a minimum of 9 subcultures. Nearly 30 more strains have lost their vigor or have become aconidial.